Development of Mithramycin Analogues with Increased Selectivity toward ETS Transcription Factor Expressing Cancers - Mitra, Prithiba (J Med Chem, 2018)
Mithramycin A (1) was identified as the top potential inhibitor of the aberrant ETS transcription factor EWS-FLI1, which causes Ewing sarcoma. Unfortunately, 1 has a narrow therapeutic window, compelling us to seek less toxic and more selective analogues. Here, we used MTMSA (2) to generate analogues via peptide coupling and fragment-based drug development strategies. Cytotoxicity assays in ETS and non-ETS dependent cell lines identified two dipeptide analogues, 60 and 61, with 19.1- and 15.6-fold selectivity, respectively, compared to 1.5-fold for 1. Importantly, the cytotoxicity of 60 and 61 is <100 nM in ETS cells. Molecular assays demonstrated the inhibitory capacity of these analogues against EWS-FLI1 mediated transcription in Ewing sarcoma. Structural analysis shows that positioning the tryptophan residue in a distal position improves selectivity, presumably via interaction with the ETS transcription factor. Thus, these analogues may present new ways to target transcription factors for clinical use.